Service Quality as A Factor Affecting the Satisfaction of Retired Civil Servants in Sharia Economic Perspective - Cut Mutiah Aksyah; Zaki Fuad; Azimah Dianah (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
dimensions of service quality, namely Tangible (physical evidence of service), Reliability, Responsiveness, Assurance and Empathy in an sharia economic perspective at PT. TASPEN (Persero) Banda Aceh. This research approach uses inferential quantitative research. The analysis technique in this study is multiple linear regression analysis by distributing questionnaires. The results of this study indicate that all service quality variables simultaneously have a positive effect on the satisfaction of Retired Civil Servant participants at PT. TASPEN (Persero) Banda Aceh. The variables of Reliability and Empathy partially have a positive effect on the retirement satisfaction of Civil Servants. While Tangible (Physical Evidence), Responsiveness and Assurance partially have no effect on the retirement satisfaction of Civil Servants at PT. TASPEN (Persero) Banda Aceh